A Hierarchy: Managing Individual Analyst Forecasts. (April 2021) - Zhou, Jie
A long line of literature documents that managers are more likely to issue guidance when the analysts' consensus forecast is optimistic. I extend this literature by providing evidence that there exists a hierarchical order by which managers respond to individual analyst forecasts. First, I find that optimism in both the majority of individual forecasts and the influential analyst's forecast are important determinants of management guidance in addition to optimism in the consensus forecasts. Second, I find that managers are more likely to issue guidance when the influential analyst forecast is optimistic, even when the consensus forecast is pessimistic. Third, when the influential analyst disagrees with the majority, managers are more willing to respond to the influential analyst. Taken collectively, this study provides new evidence on how individual analysts influence managers' voluntary disclosure and suggests a hierarchy, whereby the influential analyst's opinion is the most important factor in determining management guidance, followed by the majority or consensus.